Analyzing QRIS adoption factors and its effects on usability and decision-making in Jayapura’s MSMEs - Rofingatun, Siti; Kambuaya, Maylen K.P; Solissa, Rian Noviani (ARKA INSTITUTE, 2024)
The background of this research is based on the urgency of adopting digital payment technology to improve transaction efficiency and financial inclusion among MSMEs. The Indonesian government has initiated QRIS as a solution for easy and efficient digital payments, but its implementation among MSMEs still faces various challenges. Through a survey of 50 MSME players in Jayapura City, this study shows that the adoption of QRIS significantly affects the efficiency of financial recording and improves the accountability of financial statements. The results of this analysis show that both independent variables, namely Perceived Benefit (X1) and Perceived Ease (X2), have a significant influence on the Decision to Use QRIS (Y) among MSME players. The results of this study indicate that positive perceptions of the benefits and convenience of QRIS are closely related to the level of adoption among MSMEs. The research instrument used shows good reliability, and the regression results show that these two variables significantly influence the decision to use QRIS. This study recommends increasing digital and financial literacy to optimize QRIS adoption, and encourages stakeholders to continue promoting QRIS as part of economic digitalization.